Platelet-derived miR-142-3p induces apoptosis of endothelial cells in hypertension - Bao, H.; Yao, Q-P.; Huang, K.; Chen, X-H.; Han, Y.; Jiang, Z-L.; Gao, L-Z.; Qi, Y-X. (Cellular and Molecular Biology, 2017)
The dysfunction of endothelial cells (ECs) plays crucial roles in vascular remodeling during hypertension. Researches suggested that ECs are regulated by the circulating platelets in vivo, which may participate in abnormal EC apoptosis in hypertension. However the molecular mechanism in this process is still unclear. Here we focused on the microRNAs (miRs) in platelets, and detected the potential role and delivery mechanism of platelet-derived miRs in ECs. Using microarray, the differentially expressed profile of miRs between platelets and ECs was detected. The results revealed that compared with ECs, 67 miRs highly expressed in platelets including the most significant one- miR-142-3p. Since platelets are activated by thrombin in hypertension, we detected the miR-142-3p transferring mechanism of activated platelet, and proved that platelet-derived microparticles (PMPs), but not platelets directly, delivered miR-142-3p into ECs via cellular adherent. Furthermore, BCL2L1, an important molecule in cell apoptosis, was predicted to be a putative target of miR-142-3p by multiple algorithms. Dual luciferase reporter assays, as well as miR-142-3p mimics treatment were used to confirm the interplay between miR-142-3p and BCL2L1. Meanwhile, using in vivo hypertensive rat model, our results showed that the expression of platelet-derived miR-142-3p and the apoptosis were both significantly increased in ECs during hypertension. The present results suggested that platelet-derived miR-142-3p is delivered into ECs via PMPs, and may modulate the expression of target molecule- BCL2L1, which may subsequently display a negative function by modulating EC apoptosis in hypertension.